2006
DOI: 10.1111/j.1365-2036.2006.02782.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of oesophageal cancer: pathology, stage and clinical presentation

Abstract: SUMMARY BackgroundOesophageal adenocarcinoma is the sixth leading cause of cancer-related mortality worldwide. Previously, oesophageal cancer was mainly squamous cell, presenting late with dysphagia and weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 27 publications
5
50
1
4
Order By: Relevance
“…At initial presentation, the two most common symptoms of oesophageal cancer in our region are dysphagia and progressive weight loss, as reported in many other parts of the world [2,3] . Dysphagia usually results from advanced lesions that have led to substantial compromise in the caliber of the oesophageal lumen [3,4] .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…At initial presentation, the two most common symptoms of oesophageal cancer in our region are dysphagia and progressive weight loss, as reported in many other parts of the world [2,3] . Dysphagia usually results from advanced lesions that have led to substantial compromise in the caliber of the oesophageal lumen [3,4] .…”
Section: Discussionsupporting
confidence: 51%
“…Dysphagia usually results from advanced lesions that have led to substantial compromise in the caliber of the oesophageal lumen [3,4] . The oesophagus is not lined by a serosal layer, which allows the smooth muscles of other gastrointestinal components to stretch.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in EAC, the majority of tumors have invaded through the esophageal wall at the time of diagnosis. In a cohort of 93 patients, Schlansky and colleagues showed that 79% and 10% of symptomatic new diagnoses of EAC were T3 (tumor invades adventitia) or T4 (invasion of local structures) tumors, respectively [42]. In this setting, cure is rare.…”
Section: The Challenge Of Early Diagnosismentioning
confidence: 99%
“…Unfortunately, the number of tumors detected at this stage is low (<1%) [42]. The challenge we face is how to detect EAC at an earlier stage, which would allow a better chance of survival and potentially more localized and less invasive endoscopic treatment.…”
Section: The Challenge Of Early Diagnosismentioning
confidence: 99%
“…Unfortunately the majority of esophageal adenocarcinoma has invaded through the esophageal wall at the time of diagnosis. 7 Surgery remains the main stay of the treatment for resectable diseases but most patients in western countries present with locally advanced disease and 5 year survival rate with surgery alone are dismal at approximately 25%. 8 Outcomes for esophageal adenocarcinoma are poor because 60-70% of patients present with late stage disease, too advanced for treatment with curative intent.…”
Section: Introductionmentioning
confidence: 99%